2008
DOI: 10.1258/td.2007.070271
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological shift, seasonal variation and antimicrobial susceptibility patterns among enteric fever pathogens in south India

Abstract: Between January 2005 and December 2006, a higher incidence of paratyphoid fever (53.8%) compared to typhoid fever (44.9%) has been observed at a tertiary hospital in South India. A definite seasonal pattern of incidence is seen in paratyphoid fever (peak incidence during October-December, i.e., post monsoon period) but not in typhoid fever. Decreased fluoroquinolone susceptibility is much higher in S. Paratyphi A (98.8%) as compared to S. Typhi (46.5%). These findings are of importance in therapeutic decision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Resistance to nalidixic acid among S. Paratyphi isolates was recently found to be more common than among S. Typhi isolates obtained from hospitalized patients in India and Nepal, while MDR was relatively rare among both pathogens. [15][16][17] In contrast, all S. Paratyphi A isolates identified in this study were susceptible to all antimicrobial agents tested, while 40% of S. Typhi isolates were MDR. This study further observed an association between MDR S. Typhi strains and prior antibiotic use, which has been demonstrated previously with other Gram-negative enteric pathogens.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Resistance to nalidixic acid among S. Paratyphi isolates was recently found to be more common than among S. Typhi isolates obtained from hospitalized patients in India and Nepal, while MDR was relatively rare among both pathogens. [15][16][17] In contrast, all S. Paratyphi A isolates identified in this study were susceptible to all antimicrobial agents tested, while 40% of S. Typhi isolates were MDR. This study further observed an association between MDR S. Typhi strains and prior antibiotic use, which has been demonstrated previously with other Gram-negative enteric pathogens.…”
Section: Discussionmentioning
confidence: 68%
“…10 Several Asian countries have reported the emergence of fluoroquinolone resistance among S. Paratyphi. [11][12][13][14][15][16][17] The overall situation has heightened the need to identify prevention measures, including vaccines, against a variety of invasive enteric pathogens. 10,18,19 However, a vaccine against paratyphoid fever is not yet available, and immunization with currently available vaccines against typhoid fever does not provide cross-protection against paratyphoid fever.…”
Section: Introductionmentioning
confidence: 99%
“…Hospital-based studies from India demonstrated great regional variation in proportion of enteric fever attributed to S. Paratyphi A as 38.7 and 54.5% of enteric fever isolates were identified as S. Paratyphi A in South and West India respectively compared to only 21.0 and 24.3% in East and North India respectively [18]–[21]. The proportion of S. Paratyphi A in Pakistan was similar to East and North India, where a prospective country-wide hospital-based study identified 28.9% of enteric fever isolates as S. Paratyphi A between 2001 and 2006 [22].…”
Section: Resultsmentioning
confidence: 99%
“…[8] The incidence in South Asia is 40–80 cases/100,000 person-years and is increasing where the disease burden is high. [9] In 1975, S. paratyphi was reported to be the third most common, while S. typhi constituted 57% of the 47 human serotypes at that time. [10] The prevalence of paratyphoid fever is most commonly reported with S paratyphi A.…”
Section: Discussionmentioning
confidence: 99%
“…[18] In Karnataka, ≥50% isolates were because of S. paratyphi and a seasonal increase (monsoon) was also observed. [9] In hospital-based studies, 10–54.5% of enteric fever cases are attributable to paratyphoid fever. [15]…”
Section: Discussionmentioning
confidence: 99%